Televised Accounting Instruction, Attitudes and Performance: A Field Experiment. - Snowball, Doug; Collins, William A. (The Accounting Review, 1980)
ABSTRACT: This paper describes a field experiment undertaken to assess effects of televised introductory accounting instruction. The semantic differential was employed in the measurement of students' attitudes toward the accounting profession, accounting as a major, and the accounting lecturer. Attitudes and exam performance of students who received televised instruction were compared with those of students who received instruction by conventional methods. In both cases, instruction was provided within a large group context. No statistically significant differences were found in attitudes toward either majoring in accounting or the lecturer, nor was there a statistically significant difference in exam performance. However, significantly more favorable attitudes toward the accounting profession were associated with those who received televised instruction.